Dominant immune cells in pregnancy and pregnancy complications: T helper cells (TH1/TH2, TH17/Treg cells), NK cells, MDSCs, and the immune checkpoints. (6th November 2022) - Esparvarinha, Mojgan; Madadi, Sahar; Aslanian‐Kalkhoran, Lida; Nickho, Hamid; Dolati, Sanam; Pia, Helen; Danaii, Shahla; Taghavi, Simin; Yousefi, Mehdi
Abstract: Pregnancy problems including recurrent pregnancy loss, repeated implantation failure and pre‐eclampsia are common problems in the reproductive ages. Different reasons such as genetic, immunological, and environmental agents and also infections could develop these complications. In those cases in which the cause of the abortion is diagnosed, the chance of a successful pregnancy is increased by eliminating defective factors. However, in patients with unknown causes, there may be an imbalance in immune cells pattern. As a matter of fact, an inappropriate immune response is often associated with a failed pregnancy. Hence, the focus of treatment is to increase tolerance, not to suppress maternal immune system. These findings are linked to an elevated number of Treg cells and immune checkpoints through normal pregnancy. The present review discusses the balance of myeloid‐derived suppressor cells, natural killer cells, T cells, and immune checkpoints, and also targeting them to maintain pregnancy and prevent associated complications.